Access to Population-Level Signaling as a Source of Inequality - Immorlica, Nicole; Ligett, Katrina; Ziani, Juba (2018)
We identify and explore diﬀerential access to population-level signaling (also known as information design) as a source of unequal access to opportunity. A population-level signaler has potentially noisy observations of a binary type for each member of a population and, based on this, produces a signal about each member. A decision-maker infers types from signals and accepts those individuals whose type is high in expectation. We assume the signaler of the disadvantaged population reveals her observations to the decision-maker, whereas the signaler of the advantaged population forms signals strategically. We study the expected utility of the populations as measured by the fraction of accepted members, as well as the false positive rates (FPR) and false negative rates (FNR). We ﬁrst show the intuitive results that for a ﬁxed environment, the advantaged population has higher expected utility, higher FPR, and lower FNR, than the disadvantaged one (despite having identical population quality) and that more accurate observations improve the expected utility of the advantaged population while harming that of the disadvantaged one. We next explore the introduction of a publicly observable signal, such as a test score, as a potential intervention. Our main ﬁnding is that this natural intervention, intended to reduce the inequality between the populations’ utilities, may actually exacerbate it in settings where observations and test scores are noisy.